Artificial Intelligence and Machine Learning in Defense Applications IV 2022
DOI: 10.1117/12.2642003
|View full text |Cite
|
Sign up to set email alerts
|

Action recognition algorithm from visual sensor data for contactless robot control systems

Abstract: Automation of production processes using robots is a priority for the development of many industrial enterprises. Robotization is aimed at freeing a person from dangerous or routine work. At the same time, robots are able to perform tasks more efficiently than human, and the collaboration of a human and a robot allows to combine the strengths and effectiveness of robots and human cognitive ability into a single flexible system, and as a result, organize flexible methods of automation and reconfiguration of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The experiment showed that remote gesture control systems could control the robot. The presented improved algorithm showed an almost 2% higher efficiency than in previous studies [19].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The experiment showed that remote gesture control systems could control the robot. The presented improved algorithm showed an almost 2% higher efficiency than in previous studies [19].…”
Section: Discussionmentioning
confidence: 57%
“…Each action was performed 4 times by 15 people. Thus, 480 videos of gesture commands were obtained [19].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we use an approach based on the classical Laplace pyramid [1] described in Section 2.1 to fuse data. The fused data is preprocessed in the next step by a two-way Gabor Quaternion Fourier Transform (GQFT) in [2,3,4] and calculating 3D local binary dense micro-block difference. Also, we obtain human skeleton data using a convolutional neural network or some motion capture devices (for example, Kinect) [4].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The fused data is preprocessed in the next step by a two-way Gabor Quaternion Fourier Transform (GQFT) in [2,3,4] and calculating 3D local binary dense micro-block difference. Also, we obtain human skeleton data using a convolutional neural network or some motion capture devices (for example, Kinect) [4]. Next, the 3D local binary dense microblock difference descriptor and the skeletal descriptor are concatenated into a single feature vector.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Creating an interface that is understandable and ergonomic for a person, in this vein, becomes an almost impossible task. One solution to this problem can be to control the device using a command of gestures given by a person [1][2][3][4]. This artificial cognitive "sensory perception" or ability is a communication channel between humans and robots.…”
Section: Introductionmentioning
confidence: 99%